Poverty, Religious Differences, and Child Mortality in the Early Twentieth Century: The Case of Dublin. Issue 3 (4th May 2017) - Connor, Dylan Shane
Abstract : Across many cities in the early twentieth century, one in five children died before their fifth birthday. There is much we do not know about how infant and child mortality was reduced or why it declined at different rates across populations. This article investigates mortality using data from 13, 247 families in Dublin City in the 1900s with a novel approach that incorporates geographic information systems, spatially derived predictors, and multilevel modeling. In the early twentieth century, Dublin had one of the highest early-age mortality rates in the British Empire. Whereas experts attributed the death of young children to the unhygienic behaviors of indigenous Roman Catholics, others made claims of a social injustice rooted in economic inequality and the indifference of public authorities toward the health of the lower classes. This article finds that high Catholic mortality was mainly driven by poverty and the conditions engendered by residential segregation. Low mortality rates among Dublin's small Jewish population are not easily explained by location or economic characteristics.